Comparison of Elementary School, High School, and Teenage Students' Receptions to Modern Indonesian Literature in East Nusa Tenggara - Orance Ferderika Balan; Mas'ulah Mas'ulah (Politeknik Siber Cerdika Internasional, 2026)
Background: The development of literacy education in Indonesia highlights the need to understand how readers from diverse age groups engage with literary texts, particularly in culturally rich regions such as East Nusa Tenggara. Objective: This study analyzes readers' reception of modern Indonesian literature among three age groups in East Nusa Tenggara: elementary school students, senior high school students, and general youth. Methods: A descriptive qualitative approach was employed using Likert-scale questionnaires, semi-structured interviews, and participatory observation. Quantitative data were analyzed descriptively, while qualitative data underwent thematic coding with triangulation validation. Results: Reception develops according to age and social context. Elementary school students emphasize moral values such as honesty and learning motivation. Senior high school students engage more critically with narrative conflict and character development. General youth readers offer reflective interpretations centered on cultural values and local identity. The honesty aspect obtained the highest Likert mean (M = 4.30), followed by learning motivation (M = 4.21) and empathy (M = 4.18). Implications: Modern Indonesian literature serves as an adaptive medium for fostering literacy, character development, and cultural identity across age groups. Literary integration in educational contexts should consider readers' developmental characteristics to maximize its educational and cultural impact.